Sensitivity enhancement of Si-29 double-quantum dipolar recoupling spectroscopy by Carr-Purcell-Meiboom-Gill acquisition method - Goswami, M.; Madhu, Perunthiruthy K.; Dittmer, J.; Nielsen, N. C.; Ganapathy, Subramanian (Chemical Physics Letters, 2009)
An enhancement in the detection sensitivity of dipolar recoupled Si-29 double-quantum magic-angle spinning experiment is shown with a Carr-Purcell-Meiboom-Gill (CPMG) train of pi pulses during the acquisition period. Symmetry-adapted pulse schemes, such as POST-C7 and SR26(4)(11), are used for the double-quantum excitation. Application of POST-C7-CPMG method for framework characterisation is demonstrated in the disordered and catalytically important ZSM-5 molecular sieve. Based on the observed double-quantum dipole-dipole correlations and the known T-site Si connectivities, the assignment of all the signals is made for the orthorhombic phase of the as-synthesised (CN form) material. (C) 2009 Elsevier B. V. All rights reserved.